Determinan Prevalensi Balita Stunting di Indonesia Tahun 2021 - Priatmadani, Priatmadani; Anjarweni, Hanifah Ukti; Putri, Shalihati Melani; Pramana, Anugerah Surya; Palupi, Retno; Budiasih, Budiasih (Seminar Nasional Official Statistics, 2023)
Stunting is a disorder of child growth and development caused by inadequate nutritional intake and is characterized by below standard height. The stunting prevalence rate in Indonesia still exceeds the WHO recommendation, which is 20%, which is 24.4%. The problem of stunting in Indonesia is related to food security, economic and social conditions of the community. From this aspect, variables that are suspected of influencing stunting in Indonesia include food expenditure, food insecurity, PMT in KEK pregnant women, food insufficiency, level of education, and proper sanitation, the data of which was obtained from the Ministry of Health and BPS. The results of mapping the percentage of stunting show that areas that need to accelerate the reduction of stunting are in the eastern provinces of Indonesia and there is a spatial autocorrelation in the percentage of stunting between provinces in Indonesia. Based on the Spatial Autoregressive (SAR) model, only the education level variable has no significant effect and the percentage of stunting in a province in Indonesia will have a significant positive effect on the percentage of stunting in surrounding provinces.